The Influence of Knowledge Management Capability, Business Continuity Readiness and Innovation Capability on Organizational Resilience in the Health Sector - Iwan Henri Kusnadi; Ilham Arief; Desi Kristanti; Budi Yulhasfi Febrianto; Ainil Mardiah (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Within the context of the healthcare industry, the purpose of this study is to evaluate the influence that Knowledge Management Competence (KMC), Business Continuity Readiness (BCR), and Innovation Capability (IC) have on Organizational Resilience (OR). Both the quantitative methodology and the survey method were used in order to collect responses from individuals who were administrative personnel and health care professionals working for a variety of health care organizations. The selection of the sample was based on the purposive sampling approach, and the data were collected via the use of online questionnaires. The information was subjected to a number of different linear regression analyses. The findings provide credence to the notion that the capabilities of Knowledge Management Capability, Business Continuity Readiness, and Innovation Capability all have a substantial and favorable impact on the resilience of an organization, partly and concurrently. According to the findings of this research, the relationship between the coefficient of variation of organizational resilience and three distinct factors may be explained by the fact that business continuity readiness is the single most important factor in organizational resilience. According to the findings of the research, the foundation for the construction of a health care organization that is more resilient and flexible is the development of capabilities for knowledge management, preparedness for business continuity, and innovation. This is done in an effort to guarantee the quality of services in the face of a variety of changes and emergency situations.